How to develop and manage your own community seed bank: Farmers’ handbook (updated version). Establishing a community seed bank: Booklet 1 of 3 - Vernooy, Ronnie; Bessette, Guy; Sthapit, Bhuwon R.; Dibiloane, Angeline; Lettie Maluleke, Nkat; Abner Matelele, Lehlogonolo; Mokoena, Mpolokeng Lydia; Phora, George; Sema, Precious; Thabo, Tjikana (Bioversity International, 2020)
This handbook is a companion to Vernooy, R., Sthapit, B. and Bessette, G. (2020). Community seed banks: concept and practice. Facilitator handbook (updated version). Bioversity International, Rome, Italy (https://hdl.handle.net/10568/81286). The three booklets making up this handbook were written and designed for rural producers who are interested in establishing, supporting, and managing a community seed bank. Each booklet focuses on a theme presented by the members of a community seed bank in Africa, Asia, and Latin America. Booklet 2 is available at: http://hdl.handle.net/10568/92001; Booklet 3 is available at: http://hdl.handle.net/10568/92002 . The booklets are available also in Spanish and French. Spanish version: https://hdl.handle.net/10568/93189 ; French version: https://hdl.handle.net/10568/92875. Translation and adaptation to the local language is encouraged. If you would like to receive a hard copy of the booklets or give feedback or suggestions for improvement, please contact bioversity@cgiar.org